Use of the first-acquired language modulates pupil size in the processing of island constraint violations - Martohardjono, Gita; Johns, Michael A.; Franciotti, Pamela; Castillo, Daniela; Porru, Ilaria; Lowry, Cass (Frontiers in Psychology, 2023)
Traditional studies of the population called "heritage speakers" (HS) have treated this group as distinct from other bilingual populations, e.g., simultaneous or late bilinguals (LB), focusing on group differences in the competencies of the first-acquired language or "heritage language". While several explanations have been proposed for such differences (e.g., incomplete acquisition, attrition, differential processing mechanisms), few have taken into consideration the individual variation that must occur, due to the fluctuation of factors such as exposure and use that characterize all bilinguals. In addition, few studies have used implicit measures, e.g., psychophysiological methods (ERPs; Eyetracking), that can circumvent confounding variables such as resorting to conscious metalinguistic knowledge. This study uses pupillometry, a method that has only recently been used in psycholinguistic studies of bilingualism, to investigate pupillary responses to three syntactic island constructions in two groups of Spanish/English bilinguals: heritage speakers and late bilinguals. Previous analyses of this same population revealed group differences in the processing of the same structures. The present study is a follow-up in which usage variables, current and historical use of Spanish were added as variables. Data were analyzed using generalized additive mixed effects models (GAMMs) and two models were created and compared to one another: one with group and the other with current and historical use of Spanish as terms. Results show that group-based models generally yield conflicting results while models collapsing groups and having usage as a predictor yield consistent ones. In particular, current use predicts sensitivity to L1 ungrammaticality across both HS and LB populations. We conclude that individual variation, as measured by use, is a critical factor that must be taken into account in the description of the language competencies and processing of heritage and late bilinguals alike.